2014
DOI: 10.1371/journal.pone.0094850
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Physiological Correlates of Neuromuscular Electrical Stimulation in COPD: A Pilot Study

Abstract: RationaleNeuromuscular electrical stimulation (NMES) of the lower limbs is an emerging training strategy in patients with COPD. The efficacy of this technique is related to the intensity of the stimulation that is applied during the training sessions. However, little is known about tolerance to stimulation current intensity and physiological factors that could determine it. Our goal was to find potential physiological predictors of the tolerance to increasing NMES stimulation intensity in patients with mild to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…The levels of force evoked by NMES were notably lower than those observed in healthy subjects at first NMES use [ 22 ], but actually close to those reported in other chronic diseases. In fact, with a mean of 6.2 ± 9.0% MVC for multipath NMES (but up to 16.4% and 30.6% of MVC in two patients), the force levels obtained in this pilot study and particularly with the multipath system were similar to those observed at first NMES application in patients with COPD [ 17 , 28 ]. It is worth noting that an increase in current intensity is largely expected in the days following the very first NMES session, which could reach >+10 mA for the first week [ 28 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The levels of force evoked by NMES were notably lower than those observed in healthy subjects at first NMES use [ 22 ], but actually close to those reported in other chronic diseases. In fact, with a mean of 6.2 ± 9.0% MVC for multipath NMES (but up to 16.4% and 30.6% of MVC in two patients), the force levels obtained in this pilot study and particularly with the multipath system were similar to those observed at first NMES application in patients with COPD [ 17 , 28 ]. It is worth noting that an increase in current intensity is largely expected in the days following the very first NMES session, which could reach >+10 mA for the first week [ 28 ].…”
Section: Discussionsupporting
confidence: 67%
“…In fact, with a mean of 6.2 ± 9.0% MVC for multipath NMES (but up to 16.4% and 30.6% of MVC in two patients), the force levels obtained in this pilot study and particularly with the multipath system were similar to those observed at first NMES application in patients with COPD [ 17 , 28 ]. It is worth noting that an increase in current intensity is largely expected in the days following the very first NMES session, which could reach >+10 mA for the first week [ 28 ]. Our current results are thus of importance since we demonstrated that it was possible to evoke visible muscle contractions in about half of the patients when initially exposed to NMES.…”
Section: Discussionsupporting
confidence: 67%
“…Only one patient withdrew due to muscle discomfort which was reported in her second week of use. Tolerance to NMES exercise is individual-specific with around 10% of older adults and those with chronic diseases being unable to tolerate NMES exercise [29,30]. In cancer patients, this estimate may be higher particularly amongst those undergoing treatment, which may exacerbate tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a habituation period of 1-2 may be required to achieve these strengthening thresholds and to identify nonresponders [19]. Indeed, 10% of patient groups and elderly cohorts do not tolerate NMES [19,39] and an extended intervention period may be required to realise the true magnitude of adaptation to NMES stimulus in the elderly [40]. Therefore, habituation to NMES should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%